The Effect of Financial Leverage, Employee Stock Ownership Program and Firm Size on Firm Performance of Companies Listed in Indonesia Stock Exchange - Nurainun Bangun; F.X. Kurniawan Tjakrawala; Kurniati W. Andani; Linda Santioso (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2017)
The purpose of this research is to examine and to obtain affected empirical evidence of financial leverage, firm size and employee stock ownership program (ESOP) to firm performance in manufacturing company in Indonesian Stock Exchange on 2013-2015. Independent variables in this research are Financial Leverage (DER), Firm Size and Employee Stock Ownership Program (ESOP). Dependent variables in this research are Return on Assets (ROA) and Return On Equity (ROE). The results Showed that the simultaneous test of three independent variables Significantly afftected to the ROA and ROE. The partial tests of Financial Leverage (proxy DER) and Firm Size Significantly affected to ROA and ROE. But, the results Showed that the Employee Stock Ownership Program (ESOP) did not Affect to ROA and ROE.